A COMPARATIVE STUDY OF SOME OF THE SPECIAL FITNESS AND SKILL - OTHMAn, KHALID HASSAN; MOHAMMED, DINDAR FAIDHI (Journal of Duhok University, 2020)
The objective of the research is to identify the most important elements of physical fitness and skill of kung Fu and kickboxing for the youth. Discover the differences in some special fitness and skill elements between the kung Fu and kickboxing players of Duhok Sports Club. The researchers hypothesized that there were significant differences in some elements of physical fitness and skill among the players of Kung Fu Kickboxing for Duhok Sports Club. The research community includes the 120 players of Duhok Sports Club Kung Fu and Kickboxing, representing all age groups. The sample of the research was deliberately selected from the Kung Fu and Kickboxing players for the youth category. They numbered 34 players and 17 Kung Fu players and 17 for Kickboxing players. The researchers used the arithmetic mean and the standard deviation of the percentage and the value of two separate and linked samples, And the researchers concluded that the kung Fu superiority of the players on the kickboxing in the straight punch test in 32 punch on four cushions to measure the fitness of the special, the test of the straight punch during 30 th for measuring speed and the parallel man to measure the flexibility of the two men. There was no superiority in the results of Kung Fu players The Cake Boxing in the rest of the special fitness elements Kung Fu players also outperformed kickboxing players in straight punk skill. However, there was no superiority in the results of kung Fu and kickboxing players in other motor skills.